Krisis Spiritualitas Siswa di Era Digital: Pembelajaran PAI Reflektif Sebagai Solusi Penguatan Kompetensi Iman dan Akhlak. - Siti Patimah; Dika Merlianda; Nurul Zaman (Jurnal Budi Pekerti Agama Islam, 2025)
The spiritual crisis among students in the digital age is increasingly evident through a decline in interest in worship, low moral awareness, and an increase in individualistic lifestyles that affect the formation of faith and moral competence. This condition requires the development of Islamic Religious Education (IRE) learning that is not only oriented towards cognitive understanding, but also fosters a deep spiritual awareness among students. This study aims to analyze the role of reflective-based PAI learning as a solution in strengthening students' faith and moral competence amid digital challenges. The method used is library research by examining books, curriculum policies, and relevant national and international journal articles over the last ten years. The results of the study show that the reflective approach, through activities such as muhasabah, personal journals, value dialogues, and tadabbur experiences, is able to increase self-awareness, faith appreciation, and strengthen social morals more effectively than conventional learning, which is one-way and teacher-centered. In addition, the integration of reflective values has been proven to support the achievement of basic PAI competencies as mandated in KMA No. 183/2019, especially in the spiritual and affective domains. These findings imply that PAI learning in the digital age needs to adopt a more participatory, contemplative, and experience-based design in order to foster character building.